At the Dawn of Renewal: Temporary Notation and Cosmic Inquiry in Costa Rican Poetry. Azofeifa, Debravo, Amighetti and Chen Sham - Chen Sham, Jorge (2020)
This article, which weaves relationships and dialogues with the one published by Isaac Felipe Azofeifa in number 2 of the Revista de Filología y Lingüística de la Universidad de Costa Rica (1975), resumes one of the explanations in the self-reading of his writing, offered by the poet himself. In this way, with the purpose of drawing an interpretive line, the topic of dawn is addressed in a series of Costa Rican poets (Azofeifa, Debravo, Amighetti and Chen Sham), in whose poems the morning is established as the starting point of a reflection and a celebration that also involves the poetic self. The metaphysical or existential dimension takes all its meaning from the words of Azofeifa, to develop a rhetoric of movement and expansion, just as he proposed. The idea of ​​the homage-reply to that article implies at the same time offering a “self-explanation” to my work as a poet, because he carried it out there with his poetry; reason for which I insert myself in a theme and, following in the footsteps of Azofeifa’s, I also unfold my role as creator.